Understanding the Problem of Islamic Womens Leadership in Indonesia: An Ecofeminism Analysis - Muhammad, Iqtamar; A, Andi (Islam Transformatif : Journal of Islamic Studies, 2022)
This paper describes the problems of Muslim womens leadership in Indonesia from an ecofeminist perspective. the issue changed preceded by a gender discourse that advanced in Indonesia, then discussing the connection between men and women, to research about the emergence of the issues of Muslim women's leadership in Indonesia through an ecofeminist approach. Consequently, troubles related to leadership for women need to be addressed and minimized with a purpose to recognize the standards of justice and equality as an excellent way to get the same opportunities to develop up to become leaders for Muslim women in Indonesia. This paper makes use of the kind of literature research. Thus, content analysis, critical discourse analysis, and deductive and inductive are used with the ecofeminist approach to reply to the problems experienced by using Muslim women in Indonesia. Tulisan ini memaparkan permasalahan kepemimpinan perempuan Muslim di Indonesia dari perspektif ekofeminis. Perubahan isu tersebut diawali dengan wacana gender yang berkembang di Indonesia, kemudian membahas keterkaitan antara laki-laki dan perempuan, hingga penelitian tentang munculnya isu-isu kepemimpinan perempuan Muslim di Indonesia melalui pendekatan ekofeminis. Oleh karena itu, permasalahan yang terkait dengan kepemimpinan bagi perempuan perlu ditanggulangi dan diminimalisir dengan tujuan untuk mengakui standar keadilan dan kesetaraan sebagai cara terbaik untuk mendapatkan kesempatan yang sama untuk berkembang menjadi pemimpin bagi perempuan Muslim di Indonesia. Makalah ini menggunakan jenis penelitian kepustakaan. Dengan demikian, analisis isi, analisis wacana kritis, dan deduktif dan induktif digunakan dengan pendekatan ekofeminis untuk menjawab permasalahan yang dialami perempuan muslim di Indonesia.